MORPHOLOGICAL CHARACTERISTICS OF MANDIBULAR BONE REGENERATION IN AN EXPERIMENT USING NATURAL COLLAGEN - Chelpanova, I.V. (World of Medicine and Biology, 2024)
The purpose of the study was to determine the dynamics of histoarchitectural reconstructions of bone-ceramic regeneration after augmentation of an experimental defect of the lower jaw of a rabbit with an osteoplastic material – natural collagen. Despite the already-known results of using osteoplastic materials in clinical practice, complete and high-quality regeneration of the bones of the maxillofacial area, its mechanisms, and dynamics remain incompletely understood and require clarification and detailing. Sexually mature male rabbits aged 6–7 months, weighing 2.5–3 kg, were used for the study. The control group included animals with a bone tissue defect that healed under a blood clot. The experimental group consisted of rabbits in which the bone defect was filled with natural collagen. Control of the post-traumatic state of bone tissue in the area of the defect was carried out for 84 days. Ultrastructural changes were studied by scanning electron microscopy. Three parameters were calculated to determine changes in the composition of the regenerate. The data were analyzed using Student’s t-test. The difference at p